(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Study Objectives Job satisfaction has been shown to be influential on staff retention level and work productivity, but no study has been conducted with physiotherapists in Saudi setting.Design A qualitative research design was used in this study.Methods A qualitative study using snowball sampling was done in two phases. First phase was a focus group done with five physiotherapists studying at MSc and PHD level in the UK to refine the topic guide and provide the researcher with interview experience and the second stage was Skype and telephone semi structured interviews with twelve physiotherapists working at four different hospitals in Riyadh city. Semi structured interview was conducted to gain in-depth insight of the physiotherapists regarding job satisfaction. Thematic analysis was used to obtain the main themes.Results Saudi physiotherapists are generally satisfied with their job. Main reasons for satisfaction were patient satisfaction, salary and relation with colleagues. They considered injustice in the new pay hierarchy system, autonomy, high workload and poor public recognition as main factors that might lead to poor satisfaction at work. Saudi physiotherapists in this study did not consider immigration to work abroad as an option however they suggest that actions should be taken by stakeholder to improve their satisfaction and allow them to provide better quality of service for patients .Future research is required to explore the opinions of physiotherapists working in both governmental and private setting across the kingdom to identify the influence of clinical settings on job satisfaction and how the physiotherapists view their role to develop the profession in KSA.Conclusion The study results has revealed that Saudi physiotherapists working in Riyadh city are satisfied, main reasons for satisfaction were patient satisfaction, salaries and relation with colleagues. They considered injustice in the new pay hierarchy, autonomy, high workload and poor public recognition as the main factors that might lead to poor satisfaction. Saudi physiotherapists in this study did not consider immigration to work abroad as an option however they suggest that actions should be taken by stakeholder to improve their satisfaction by improving the public awareness, implement fairer pay hierarchy and decrease the workload to allow them to provide better quality of care for patients .Future research is required to explore the opinions of physiotherapists working in both governmental and private setting to identify the influence of clinical settings on job satisfaction and how the physiotherapists view their role to develop the profession in KSA.